THE CRISIS AND THE VOICES LEFT BEHIND (Andamios, Revista de Investigación Social, 2010)
An economic crisis can highlight some of the excesses that must be fought in the present and avoided in the future. They are not a consequence of the action of a specific or particular thought. This paper pays attention to different voices: those who ask for the right to credit, those who want a limit to private property, and those who demand responsibilities from one to another, and who present other development models.
Keywords: Credit; development; human rights; property; responsibility